2010
DOI: 10.1523/jneurosci.3225-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Response Characteristics of Basolateral and Centromedial Neurons in the Primate Amygdala

Abstract: Based on cellular architecture and connectivity, the main nuclei of the primate amygdala are divided in two clusters: basolateral (BL) and centromedial (CM). These anatomical features suggest a functional division of labor among the nuclei. The BL nuclei are thought to be involved primarily in evaluating the emotional significance or context-dependent relevance of all stimuli, including social signals such as facial expressions. The CM nuclei appear to be involved in allocating attention to stimuli of high sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 52 publications
5
69
0
Order By: Relevance
“…Our analysis revealed that there are fewer VLPFC neurons responsive to the vocalization component of the audiovisual stimulus, or its change, compared with the number of neurons responsive to the face or the change of the face. These results parallel findings of greater numbers of visual unimodal responses compared with auditory unimodal responses in VLPFC (Sugihara et al, 2006;Diehl and Romanski, 2014), and in the monkey amygdala, another face-vocalization integration area, where many neurons are robustly responsive to faces (Gothard et al, 2007;Kuraoka and Nakamura, 2007;Mosher et al, 2010), but fewer neurons respond to corresponding vocalizations (Kuraoka and Nakamura, 2007). Moreover, even human subjects fare better at face recognition than voice recognition in many situations (Colavita, 1974;Hanley et al, 1998;Joassin et al, 2004;Calder and Young, 2005;Sinnett et al, 2007).…”
Section: Auditory Discrimination In Nonhuman Primatessupporting
confidence: 71%
“…Our analysis revealed that there are fewer VLPFC neurons responsive to the vocalization component of the audiovisual stimulus, or its change, compared with the number of neurons responsive to the face or the change of the face. These results parallel findings of greater numbers of visual unimodal responses compared with auditory unimodal responses in VLPFC (Sugihara et al, 2006;Diehl and Romanski, 2014), and in the monkey amygdala, another face-vocalization integration area, where many neurons are robustly responsive to faces (Gothard et al, 2007;Kuraoka and Nakamura, 2007;Mosher et al, 2010), but fewer neurons respond to corresponding vocalizations (Kuraoka and Nakamura, 2007). Moreover, even human subjects fare better at face recognition than voice recognition in many situations (Colavita, 1974;Hanley et al, 1998;Joassin et al, 2004;Calder and Young, 2005;Sinnett et al, 2007).…”
Section: Auditory Discrimination In Nonhuman Primatessupporting
confidence: 71%
“…This interpretation would be similar to forward models of the motor system where information about the produced movement is analyzed to produce predictions about the outcome (44,45). In the current case, the outcome might be social responses of a peer, and this information, which was shown to reside in the same circuits (6,(28)(29)(30)(31)(32)(33), can be integrated to form a more complete interpretation of the social scene. Our finding that facial movement and social stimuli converge on single neurons in the amygdala and the dACC is in line with this suggestion and suggests a possible mechanism for how social context may shape decoding and the reciprocal response to social scenes.…”
Section: Discussionmentioning
confidence: 79%
“…More research is therefore needed in animal models where direct neuronal recordings can be combined with functional imaging, particularly in primates and for brain regions critically implicated in emotion attention (e.g. amygdala, OFC, pulvinar, and superior colliculus, as well as the various sensory cortices) (Armony, Quirk, & LeDoux, 1998;Gothard, Battaglia, Erickson, Spitler, & Amaral, 2007;Mosher, Zimmerman, & Gothard, 2010). Overall, as in other neuroscience domains, a complete picture of emotion processing and its impact on attention will require a convergence of different methodologies.…”
Section: Box Contentsmentioning
confidence: 99%